Purchasing stationary OFFICE DESIGN SYSTEMS AT AJB BUMI PUTERA Kalimalang BEKASI dari MICROSOFT VISUAL Branch BASIC 6.0 - Anak Agung Made Arioka; Marzuki SKom, MMSI (Jurnal Sistem Informasi, 2006)
Scientific research is aimed to present the report the purchase of office stationery tothe Director by using Microsoft Visual Basic 6.0. This research is a scientific researchby collecting data. The author obtained data with observation.From this research we can conclude that by using computerized will gain the ease andspeed up the process of purchasing office supplies.